2021
DOI: 10.3390/ijerph18020438
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, Prospective Memory, and Immune Status among People Living with HIV

Abstract: Background: Persons living with HIV (PLWH) frequently report sleep complaints, but objective measurements are still lacking regarding sleep continuity, total sleep time per 24 h, and the links with both prospective memory performance and HIV infection parameters. Methods: PLWH (n = 96) and control (n = 96) groups (balanced for gender and age) were monitored by 24h-actigraphy for at least seven consecutive days. The prospective memory performance was assessed through a naturalistic, activity-based task performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…Sleep disturbance, often categorized as insomnia, includes difficulty falling asleep (initiation insomnia) and nighttime awakening (maintenance insomnia), resulting in poor sleep efficiency. Similarly, Taibi (2013) used the general definition of insomnia by the American Academy of Sleep Medicine (2014b) to describe sleep disturbance, stating, “Insomnia is defined as difficulty falling asleep, difficulty staying asleep, awakening too early, or unrefreshing sleep in combination with at least one daytime symptom such as sleepiness or irritability.” In another article, Faraut et al (2021) specifically defined sleep disturbance in the PLWH population, suggesting that the “subjective measures of sleep (questionnaires, sleep diaries) show disruption of sleep continuity including difficulty falling asleep, awakening during the night, and reduced sleep time.” Although Cormier (1990) did not define sleep disturbance specifically in relation to the PLWH population, it was asserted that insomnia was a surrogate term for sleep disturbance, having stated, “Sleep disturbances encompass disorders of initiating and maintaining sleep (DIMS, insomnias)….” Yan et al (2021) , on the other hand, described sleep disturbance in the context of HIV using scores obtained from a general perception of sleep quality instrument, the Pittsburgh Sleep Quality Index (PSQI); the study found significant sleep disturbance in PLWH having scores of five or greater on the PSQI. Alternatively, Chenxi et al (2019) explained the definition of sleep disturbance in the context of HIV in a manner distinguishable from most authors, arguing that sleep disturbance is similar to a sleep disorder, including specific sleep behaviors, such as restless leg syndrome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep disturbance, often categorized as insomnia, includes difficulty falling asleep (initiation insomnia) and nighttime awakening (maintenance insomnia), resulting in poor sleep efficiency. Similarly, Taibi (2013) used the general definition of insomnia by the American Academy of Sleep Medicine (2014b) to describe sleep disturbance, stating, “Insomnia is defined as difficulty falling asleep, difficulty staying asleep, awakening too early, or unrefreshing sleep in combination with at least one daytime symptom such as sleepiness or irritability.” In another article, Faraut et al (2021) specifically defined sleep disturbance in the PLWH population, suggesting that the “subjective measures of sleep (questionnaires, sleep diaries) show disruption of sleep continuity including difficulty falling asleep, awakening during the night, and reduced sleep time.” Although Cormier (1990) did not define sleep disturbance specifically in relation to the PLWH population, it was asserted that insomnia was a surrogate term for sleep disturbance, having stated, “Sleep disturbances encompass disorders of initiating and maintaining sleep (DIMS, insomnias)….” Yan et al (2021) , on the other hand, described sleep disturbance in the context of HIV using scores obtained from a general perception of sleep quality instrument, the Pittsburgh Sleep Quality Index (PSQI); the study found significant sleep disturbance in PLWH having scores of five or greater on the PSQI. Alternatively, Chenxi et al (2019) explained the definition of sleep disturbance in the context of HIV in a manner distinguishable from most authors, arguing that sleep disturbance is similar to a sleep disorder, including specific sleep behaviors, such as restless leg syndrome.…”
Section: Resultsmentioning
confidence: 99%
“…The concept of sleep disturbance has been used inconsistently in the HIV context. Although sleep disturbanc e was most used among the terms referring to similar concepts, several other concepts have been used interchangeably, including poor sleep ( Abdu & Dule, 2020 ; Alikhani et al, 2020 ; Cody et al, 2020 ), sleep complaint ( Faraut et al, 2021 ; González-Tomé et al, 2018 ), sleep difficulty ( Mahmood et al, 2018 ), sleep disruption ( Aouizerat et al, 2021 ; Hixon et al, 2020 ), sleep pattern problem ( Bedaso et al, 2020 ), sleep alteration ( Moore et al, 2020 ), sleep disorder ( Chen et al, 2021 ; Chenxi et al, 2019 ), and insomnia ( Buchanan et al, 2018 ; Cody et al, 2020 ; Luu et al, 2022 ; Pujasari et al, 2020 ). Many previous researchers have undertaken studies to examine sleep among PLWH; however, there is no consensus on an accurate definition of sleep disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…During HIV, these perturbances are most likely due to a dysregulated immune response rather than caused by the patient's medication [70,71]. Using actigraphy, a signi cant increase in sleep onset latency (SOL) has been observed in people living with HIV compared to a gender-and age-matched control group [72]. Additionally, in a polysomnographic study of people 60 days after a SARS-CoV-2 infection, a mean SOL of approximately 90 minutes was observed [73], which is compared to 20 minutes in age-matched controls [74].…”
Section: Discussionmentioning
confidence: 99%
“…In some studies done in the SSA region, the prevalence of poor sleep quality in PLWHA ranged from 57% to 61% (171,208,209). The sleep disturbances experienced by PLWHA include hypersomnia, insomnia, difficulties in initiating sleep (longer sleep onset latency), fragmented sleep, sleep apnea, and restless leg syndrome, with variable changes in the NREM and REM sleep, as well as circadian rhythm disorders (208,(210)(211)(212)(213)(214)(215)(216).…”
Section: Prevalence Of Sleep Disorders and Nature Of Sleep Disorders ...mentioning
confidence: 99%
“…This is in contrast with some earlier studies that showed a correlation between low CD4+ cell count and poor sleep quality ( 209 , 229 , 230 ). Recently, long sleep hours were associated with low CD4+ cell count and greater severity of the disease ( 210 ).…”
Section: Specific Neurological Disturbances Related To Neuroinflammat...mentioning
confidence: 99%